Pares admissíveis, sistemas admissíveis e biálgebras na categoria dos módulos de Yetter-Drinfeld - Vieira, Larissa Hagedorn (2014)
The purpose of this work is to study the relationships between admissible pairs, systems admissible and bialgebras in the category of Yetter-Drinfeld modules, as well as some properties of the Hopf algebra associated (via bosonization) to an admissible pair. We end this dissertation with a family of examples of admissible pairs.